Identification of C3b-binding regions on herpes simplex virus type 2 glycoprotein C. - Seidel-Dugan, C (1990)
Glycoprotein C from herpes simplex viruses types 1 and 2 (gC-1 and gC-2) acts as a receptor for the C3b fragment of the third component of complement. Our goal is to identify domains on gC involved in C3b receptor activity. Here, we used in-frame linker-insertion mutagenesis of the cloned gene for gC-2 to identify regions of the protein involved in C3b binding. We constructed 41 mutants of gC-2, each having a single, double, or triple insertion of four amino acids at sites spread across the protein. A transient transfection assay was used to characterize the expressed mutant proteins. All of the proteins were expressed on the transfected cell surface, exhibited processing of N-linked oligosaccharides, and bound one or more monoclonal antibodies recognizing distinct antigenic sites on native gC-2. This suggested that each of the mutant proteins was folded into a native structure and that a loss of C3b binding by any of the mutants could be attributed to the disruption of a specific functional domain. When the panel of insertion mutants was assayed for C3b receptor activity, we identified three distinct regions that are important for C3b binding, since an insertion within those regions abolished C3b receptor activity. Region I was located between amino acids 102 and 107, region II was located between residues 222 and 279, and region III was located between residues 307 and 379. In addition, region III has some structural features similar to a conserved motif found in complement receptor 1, the human C3b receptor. Finally, blocking experiments indicated that gC-1 and gC-2 bind to similar locations on the C3b molecule.